The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/catal12070779
|View full text |Cite
|
Sign up to set email alerts
|

Employing an Artificial Neural Network in Correlating a Hydrogen-Selective Catalytic Reduction Performance with Crystallite Sizes of a Biomass-Derived Bimetallic Catalyst

Abstract: A predictive model correlating the properties of a catalyst with its performance would be beneficial for the development, from biomass waste, of new, carbon-supported and Earth-abundant metal oxide catalysts. In this work, the effects of copper and iron oxide crystallite size on the performance of the catalysts in reducing nitrogen oxides, in terms of nitrogen oxide conversion and nitrogen selectivity, are investigated. The catalysts are prepared via the incipient wetness method over activated carbon, derived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 31 publications
(41 reference statements)
0
3
0
Order By: Relevance
“…In the study of Yakub et al [ 28 ], the suggested model was used to discuss the impacts of crystallite size on the performance of copper and iron oxides in reducing NOx, as well as the construction of a prediction model that links crystallite size with H2-SCR efficiency. Monometallic as well as bimetallic catalysts doped over palm kernel shell-activated carbon were explored.…”
Section: Introductionmentioning
confidence: 99%
“…In the study of Yakub et al [ 28 ], the suggested model was used to discuss the impacts of crystallite size on the performance of copper and iron oxides in reducing NOx, as well as the construction of a prediction model that links crystallite size with H2-SCR efficiency. Monometallic as well as bimetallic catalysts doped over palm kernel shell-activated carbon were explored.…”
Section: Introductionmentioning
confidence: 99%
“…Yakub et al. 14 developed two predictive equations via an ANN technique to determine the performance of catalysts based on temperature and crystallite size. Abhyankar et al.…”
mentioning
confidence: 99%
“…Ujene and Umoh 13 developed a neural network model for predicting the percentage cost and time overrun using the site characteristics of building projects. Yakub et al 14 developed two predictive equations via an ANN technique to determine the performance of catalysts based on temperature and crystallite size. Abhyankar et al 15 identified flooded areas due to cyclonic storms using Envisat ASAR VV polarized data and an ANN.…”
mentioning
confidence: 99%